Ethanol Production in Yeasts Isolated from Fermented Kitchen Waste - S Wong; S.K Wong; J.S Bujang (ASEAN Journal on Science and Technology for Development, 2012)
Microbial ethanol is a potential substitute for the non-renewable fossil fuel which is depleting. Yeasts have been long and extensively studied for ethanol production. The objectives of this study were to isolate yeasts from fermented kitchen waste and to determine their ethanol production performances. A number of fifteen yeasts were isolated from fermented kitchen waste. The yeastswere then grouped based on their ability to ferment different types of sugars. Three yeast isolates were selected for the analysis of ethanol production. Fermentation was carried out for 72 h in yeast extract peptone dextrose broth containing 18% glucose. Fourier transform infrared attenuated total reflection spectroscopy was used to monitor the ethanol production and glucose utilization. Isolate Y4 achieved the highest ethanol production at the level of 16%, while Y6 and Y8 demonstrated 12% and 11% ethanol yields, respectively. The isolates Y4, Y6 and Y8 were identified using universal fungal primers ITS1 and ITS4. The yeast isolates were closest to Saccharomyces cerevisiae (76%), Paracoccidioides brasiliensis (56%) and Saccharomyces boulardii (64%), respectively. This studyshowed that fermented kitchen waste could serve as a good source of yeasts for ethanol production.